Students' Anxiety Levels During Online Learning During the Covid-19 Pandemic - Dewantari, Tri; Surya Putra, Barep Hapit; Bulantika, Siti Zahra (Universitas Mercu Buana Yogyakarta, 2021)
The Covid pandemic has a major impact on various fields, one of which is in the field of education. Currently, all sectors in the education sector are experiencing a period of adaptation in the implementation of the teaching and learning process. The teaching and learning process carried out online has several impacts, one of which is the anxiety experienced by students. The purpose of this study was to describe the level of anxiety of students during online learning during the Covid-19 pandemic in senior high school students. This research uses the descriptive qualitative method. Data analysis was performed using analysis from various scientific articles. The results showed that the level of student anxiety during online learning during the Covid-19 pandemic was different. This is due to the factors behind it, such as students' understanding of the material provided by the teacher, availability of internet network use, adequate facilities and infrastructure for taking part in online learning and the time for completing assignments which according to some students tends to be short.